(untitled) (Revista científica Olimpia, 2019)
An experimental study, pre-experimental modality, of intervention in the male juvenile taekwondistas belonging to the EIDE "Pedro Batista Fonseca" of Granma was carried out, with the aim of evaluating the effectiveness of the plyometrics in the development of muscle power in lower limbs. The universe consisted of 11 male youth taekwondo players and the sample, by nine of these. Muscle power was calculated from the formula proposed by Lewis: Power (kgm / sec) = 2.214 x Weight (Kg.) X square root of the flight. The test was applied at the beginning of the special varied month of the special physical preparation (IPFE), we worked with a volume of 3.5 and an intensity 3.2. The second test was at the beginning of the basic meso developer of the special physical preparation (PFE), worked with a volume of 4 and an intensity 3.75. The third test was applied at the beginning of the basic stabilizing month of the special physical preparation (PFE), in which we worked with a volume of 3.5 and an intensity 4. Descriptive statistics were used for each of the variables investigated: Absolute and relative frequencies were used; of inferential statistics the test of difference of mean and proportion. The information was processed in a computerized way, using the professional statistical program SSPS version 22.0 for Windows. The analysis of the results corroborated the effectiveness of the plyometrics applied to achieve increase muscle power in the lower limbs in male juvenile taekwondo players of the EIDE of Granma.